2017
DOI: 10.1002/bip.23076
|View full text |Cite
|
Sign up to set email alerts
|

Effect of heavy water on the conformational stability of globular proteins

Abstract: It is well established from the experimental point of view that the native state of globular proteins is more stable in heavy water than in water. No robust explanation, however, has been provided up to now. The application of the theoretical approach, originally devised to rationalize the general occurrence of cold denaturation, indicates that the magnitude of the solvent-excluded volume effect is slightly smaller in heavy water than in water and cannot explain the observed protein stabilization. The latter h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 57 publications
5
14
0
Order By: Relevance
“…Table reveals that D 2 O exposure causes Δ H U to increase by 40 and 60 kJ mol –1 for cyt c and lysozyme, respectively. This enthalpic stabilization of the native state in D 2 O is in line with earlier reports. Interestingly, enthalpic stabilization is counteracted by a Δ S U increase in D 2 O of ca. 100 J K –1 mol –1 which destabilizes the native state.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Table reveals that D 2 O exposure causes Δ H U to increase by 40 and 60 kJ mol –1 for cyt c and lysozyme, respectively. This enthalpic stabilization of the native state in D 2 O is in line with earlier reports. Interestingly, enthalpic stabilization is counteracted by a Δ S U increase in D 2 O of ca. 100 J K –1 mol –1 which destabilizes the native state.…”
Section: Resultssupporting
confidence: 93%
“…At least 60 years after its discovery, the stabilization of proteins in D 2 O remains poorly understood. In agreement with earlier work, we found that this stabilization is rooted in enthalpic effects, i.e., a larger (more positive) value of Δ H U in D 2 O than in H 2 O. Like those earlier studies, we attribute this stabilization to changes in the dissociation enthalpy of H-bonds. This effect is countered by entropy, as Δ S U is larger (more positive) in D 2 O than in H 2 O, thereby causing destabilization (Table ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…From the results presented in Figure 5, we see that the tightening of the protein structure upon water deuteration also leads to stabilization and increase of the protein melting temperature. This is in line with experimental observations, 27,28 and it is consistent with the sign of the free energies of transfer from H 2 O to D 2 O of individual amino acids in Figure 2.…”
Section: ■ Results and Discussionsupporting
confidence: 92%
“…This is in line with experimental observations, , and it is consistent with the sign of the free energies of transfer from H 2 O to D 2 O of individual amino acids in Figure .…”
Section: Resultssupporting
confidence: 92%